An investigation on user's intention to adopt accounting information system in Libyan small and medium enterprises: an analysis of structural equation modeling - Khalil Mesbah, AbdulJalil (2015)
Technology adoption study has been a constantly developing eld as this field contributes to its development with either system-focused or belief-focused. The main purpose of this study had been to investigate the attitude-behavioral-intention relationship for the adoption of Information System. In fact, this study highlighted the belief-focused aspect by using the technology acceptance model and the motivation model. Hence, the current research model proposed a combination of Technology acceptance model and motivation model to investigate the mediating effect of user's attitude between Information Technology characteristics and behavioral intention. A non-probability purposive sampling technique was applied to collect data from owners or top manager of small and medium enterprises (SMEs) in Libya. A total of 348 personal structured questionnaires were considered for the analysis with the response rate of 46.4%. Besides, a structural equation modeling approach was employed to examine the direct and the mediating eects as drawn by the hypotheses. Furthermore, with quantitative research design following positivist research paradigm, the methodology was designed to focus on the research questions and the objectives. The questionnaire was designed by using closed interval measurement scale with proper care taken in designing the survey instruments. SPSS 21.0 & AMOS 21 for structural equation modeling were utilized in confirming the hypotheses developed for the study. The findings of the study revealed that there was no direct relationship between IT characteristics and behavioral intention to adopt accounting information system (AIS). From the square multiple correlation it was found that the variables were having overall 71% of the in influence on behavioral intention to adopt AIS. Nevertheless, the results found support for the effect of user's attitude as mediator between IT characteristics and behavioral intention. Moreover, intrinsic motivation and extrinsic motivation factors of the motivation model had been found to have positive in influence in the form of attitude on owner's behavior to adopt AIS. On top of that, perceived usefulness and perceived ease of use were also found to have positive mediating effect for the relationship between IT characteristics and intention of users. The findings, thus, conrmed that user's attitude had been associated with both types of deviances. Therefore, owners should realize that a great level of AIS adoption is indeed associated with its process and context. Apart from that, attitude was found to play an important mediating effect that enhanced the perception and the motivation among decision makers to adopt information system. Therefore, in selecting the AIS adoption, SMEs need to focus on motivating their managers within the organizational context and an attempt must be made both directly and indirectly for AIS adoption.